2016
DOI: 10.1139/cjes-2015-0238
|View full text |Cite
|
Sign up to set email alerts
|

A new species of the basal plesiadapiform Purgatorius (Mammalia, Primates) from the early Paleocene Ravenscrag Formation, Cypress Hills, southwest Saskatchewan, Canada: further taxonomic and dietary diversity in the earliest primates

Abstract: The fossil record of the earliest primates, purgatoriid plesiadapiforms, has become increasingly well documented during the past two decades, but their dietary preferences remain poorly understood. While the available evidence, which consists mostly of isolated teeth and incomplete jaws with teeth, suggests that purgatoriids were insectivorous to omnivorous, we describe here a new species of Purgatorius, Purgatorius pinecreeensis sp. nov., that extends the range of purgatoriid dental disparity toward greater o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
7
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 32 publications
0
7
0
Order By: Relevance
“…SI3-1). Note that Halliday et al (2015Halliday et al ( , 2019 scored Purgatorius for the tarsal bones that Chester et al (2015) referred to this taxon (somewhat younger than P. coracis); Purgatorius is otherwise known exclusively from teeth and lower jaws Scott et al, 2016), and Chester et al (2015) referred the tarsals simply because their size fits and because they show arboreal adaptations which agree with the assumed pan-primate status of Purgatorius. Scott et al (2016: 343) preferred to call these bones "several isolated, possible This is a provisional file, not the final typeset article plesiadapiform tarsals", Plesiadapiformes being a clade or grade of stem-pan-primates or stemprimatomorphs to which Purgatorius is generally thought to belong.…”
Section: Node 155: Euarchontoglires/supraprimates (Gliriformes -Primamentioning
confidence: 92%
See 1 more Smart Citation
“…SI3-1). Note that Halliday et al (2015Halliday et al ( , 2019 scored Purgatorius for the tarsal bones that Chester et al (2015) referred to this taxon (somewhat younger than P. coracis); Purgatorius is otherwise known exclusively from teeth and lower jaws Scott et al, 2016), and Chester et al (2015) referred the tarsals simply because their size fits and because they show arboreal adaptations which agree with the assumed pan-primate status of Purgatorius. Scott et al (2016: 343) preferred to call these bones "several isolated, possible This is a provisional file, not the final typeset article plesiadapiform tarsals", Plesiadapiformes being a clade or grade of stem-pan-primates or stemprimatomorphs to which Purgatorius is generally thought to belong.…”
Section: Node 155: Euarchontoglires/supraprimates (Gliriformes -Primamentioning
confidence: 92%
“…The oldest purported total-group primatomorph -not necessarily a pan-primate [PN] (Ni et al, 2016) -is Purgatorius coracis, found in an outcrop of the Ravenscrag Formation that is at most 0.4 Ma younger than the 66.0-Ma-old Cretaceous/Paleogene boundary (Fox and Scott, 2011;Scott et al, 2016). However, Halliday et al (2015Halliday et al ( , 2019 found Purgatorius outside of Placentalia despite the presence of stem-pan-primates in their analyses.…”
Section: Node 155: Euarchontoglires/supraprimates (Gliriformes -Primamentioning
confidence: 99%
“…E). This has particularly been argued for P. pinecreeensis , which is apparently lower‐crowned with more swollen molar cusps than other species of the genus (Scott et al, ). The only other genus in the family, Ursolestes , is notably larger (944 g) and has been interpreted to exhibit more shearing potential (Fox et al, ).…”
Section: Purgatoriidae Van Valen and Sloanmentioning
confidence: 96%
“…F) are of early Paleocene age (Fox & Scott, ), implying that there is no unambiguous direct evidence that primates ever overlapped in time with non‐avian dinosaurs. However, since there is now a range of purgatoriid morphologies known from early Paleocene deposits (Fox & Scott, ; Fox, Scott, & Buckley, ; Scott, Fox, & Redman, ), it seems likely that the group originated close to the K‐Pg boundary (Silcox, ; Fox et al, ). Purgatoriids generally come out at the base of the primate tree, without special relationships to any other family, excepting possibly Micromomyidae (Bloch et al, ; Silcox, , ; Silcox et al, ; Chester et al, ).…”
Section: Purgatoriidae Van Valen and Sloanmentioning
confidence: 99%
“…We further explore the evolution of the primate body size distribution and its origins to better understand the evolutionary pressures responsible for the left-skewed pattern exhibited by extant primates. As with other mammals, fossils from the Paleocene describing primate 355 ancestors largely consist of teeth, small intact bones, and bone fragments (Fox and Scott 2011;Hunter and Pear- their radiation likely began in the late Cretaceous (Scott and Redman 2016). These species are now generally accepted as the likely earliest common ancestors of modern primates and are placed in the order plesiadapiformes (Bloch et al 2007).…”
mentioning
confidence: 99%